Upper Extremity Thrombosis Presenting as Medial Elbow Pain after Shoulder Arthroscopy - Moiz I. Manaqibwala; Irene E. Ghobrial; Alan S. Curtis (Case Reports in Orthopedics)
Deep vein thrombosis of the upper extremity is believed to be an uncommon complication of arthroscopic shoulder surgery. It most commonly presents with significant swelling and pain throughout the upper extremity. However the diagnosis can be easily missed when findings are more subtle and unrelated or the patient asymptomatic. In this study we report on 5 cases of postoperative upper extremity deep vein thrombosis (UEDVT). Each case was performed in the lateral decubitus position with an interscalene block and postoperative sling immobilization. All patients presented with a primary complaint of medial elbow pain and went on to require anticoagulation. Only one patient was found to have a heritable coagulopathy. The true incidence of thromboembolic phenomena after shoulder arthroscopy may be higher than that reported in the current literature. Therefore a high index of suspicion must be maintained when evaluating patients postoperatively to avoid misdiagnosis. Symptoms of medial elbow pain after immobilization in a sling should be considered an indication for duplex ultrasound evaluation. Ultimately, further prospective study is needed to better understand the prevalence, prevention, and management of this entity.